"Safe sex talk:" Negotiating safe sex practices in heterosexual relationships - Dako-Gyeke, P. (Mediterranean Journal of Social Sciences, 2013)
HIV and AIDS has become a gendered phenomenon, infecting more women than men, in sub-Saharan Africa, where heterosexual sex is the main mode of transmission. The complex interplay between power and gender is crucial for understanding who has control over when, where, and how sex takes place in heterosexual relationships. This study explores research participants' interpretations of cultural norms of gender, sexuality and power in scripted HIV prevention safe sex practice messages to determine if they shape individual behaviors in safe sex negotiation. Data is from 5 focus group discussions (n= 28) and in-depth interviews (n=7) involving men and women, conducted in Accra, Ghana. Data was transcribed and themes and patterns were identified. The analysis identified contradictions clouded participants' expectations (intentions) and actual sexual practices. Participants expect male sexual power and female submissiveness, yet present accounts of females actively engaging in sexual negotiations. Participants were more receptive to condom use than abstinence; specifically, the former allows access to male power while the latter controls male sexual pursuit. Yet, participants describe condom use as unpredictable and contradictory. Gendered sexual expectations, intentions and actual experiences described in this study are much more complex and require further attention. HIV interventions in Africa must pay attention to nuances in realistic accounts of heterosexual encounters to decipher complexities in the safe sex negotiation process.
Keywords: Africa; Ghana; Gender; HIV and AIDS; Safe sex